The partial ionization zone of heavy elements in F-stars: a study on how it correlates with rotation. Issue 2 (2nd July 2019) - Brito, Ana; Lopes, Ilídio
ABSTRACT: We study the relation between the internal structures of 10 benchmark main-sequence F-stars and their rotational properties. Stellar rotation of main-sequence F-type stars can be characterized by two distinct rotational regimes. Early-type F-stars are usually rapid rotators with periods typically below 10 d, whereas later-type F-stars have longer rotation periods. Specifically, and since the two rotational regimes are tightly connected to the effective temperatures of the stars, we investigate in detail the characteristics of the partial ionization zones in the outer convective envelopes of these stars, which in turn, depend on the internal temperature profiles. Our study shows that the two rotational regimes might be distinguished by the relative locations of the partial ionization region of heavy elements and the base of the convective zone. Since in all these stars is expected a dynamo-driven magnetic field where the shear layer between convective and radiative zones (tachocline) plays an important role, this result suggests that the magnetic field may be related to the combined properties of convection and ionization.